Cell-SELEX based selection and optimization of DNA aptamers for specific recognition of human cholangiocarcinoma QBC-939 cells1. Issue 17 (7th September 2015) - Wan, Jun; Ye, Ling; Yang, Xiaohai; Guo, Qiuping; Wang, Kemin; Huang, Zhixiang; Tan, Yuyu; Yuan, Baoyin; Xie, Qin
<x xml:space="preserve">Abstract</x> Aptamers recognizing human cholangiocarcinoma QBC-939 cells with high affinity and specificity were successfully generated via cell-SELEX.